Intercellular Adhesion Molecule-1 as Target for CAR-T-Cell Therapy of Triple-Negative Breast Cancer - Wei, Heng; Wang, Zeng; Kuang, Yi; Wu, Zhiguo; Zhao, Shasha; Zhang, Zongliang; Li, Hexian; Zheng, Meijun; Zhang, Nan; Long, Cheng; Guo, Wenhao; Nie, Chunlai; et al. (Frontiers in Immunology, 2020)
Triple-negative breast cancer (TNBC) is lethal malignancies with limited treatment options. Chimeric antigen receptor T (CAR-T) cell therapy is an effective immunotherapy strategy and has been demonstrated unprecedented efficacy in the treatment of hematological malignancies but has shown limited success in the management of some solid tumors. Many malignant tumors are related to increased expression of Intercellular adhesion molecule-1 (ICAM1), providing a rationale for ICAM1-specific immunotherapies for the treatment of cancer. Here, we validated the expression of ICAM1 in TNBC tissues. Subsequently, we generated a phage-displayed single chain variable fragment (scFv) library using splenocytes from ICAM1-immunised mice and selected a novel ICAM1-specific scFv (mG2-scFv) from this library. Using mG2-scFv as the extracellular antigen binding domain, we constructed ICAM1-specific CAR-T and demonstrated its robust and specific killing of TNBC cell lines in vitro. More importantly, in TNBC cancer mice model, ICAM1-specific CAR-T cells significantly reduced the growth of TNBC tumor that resulted in long-term remission and improved survival. Together, these results indicated that ICAM1-specific CAR-T cells have high therapeutic potential against ICAM1-positive TNBC tumors.